Mapping national surveillance of surgical site infections in England: needs and priorities. Issue 4 (December 2018) - Troughton, R.; Birgand, G.; Johnson, A.P.; Naylor, N.; Gharbi, M.; Aylin, P.; Hopkins, S.; Jaffer, U.; Holmes, A.
Summary: Background: The rise in antimicrobial resistance has highlighted the importance of surgical site infection (SSI) prevention with effective surveillance strategies playing a key role in improving patient safety. Aim: To map national needs and priorities for SSI surveillance against current national surveillance activity. Methods: This study analysed SSI surveillance in National Health Service (NHS) hospitals in England covering 23 surgical procedures. Data collected were: (i) annual number of procedures, (ii) SSI rates from national reports, (iii) national reporting requirement (mandatory, voluntary, not offered), (iv) priority ranking from a survey of 84 English NHS hospitals, (v) excess length of stay and costs from the literature. The relationships between estimated SSI burden, national surveillance activity, and hospital-reported priorities were explored with descriptive and univariate analyses. Findings: Among the 23 surgical categories analysed, top priority ranking by hospitals was associated only with current surveillance ( r = 0.76, P < 0.01) and mandatory reporting (33% vs 8 and 4%, P = 0.04). Percentage of hospitals undertaking surveillance, mandatory reporting, and the selection of priorities did not match SSI burden. Large bowel surgery (LBS, voluntary) and caesarean section (not offered) were the two highest contributors of total SSIs per annum, with 39, 000 (38%) and 17, 000 (16%) respectively, while the four orthopaedic categories (all mandatory) contributed 5000 (5%). LBS also had the highest associated costs (£119 million per annum). Conclusion: Current surveillance and future priorities were not associated with SSI rate, volume, or cost to hospitals. The two highest contributors of SSIs and related costs have no (caesarean section) or limited (LBS) coverage by national surveillance.